Optimism in Orphanage Children Reviewed from Self-Acceptance and Self-Esteem - Nashori, Fuad; Sabila, Dina (Psychosophia: Journal of Psychology, Religion, and Humanity, 2024)
Children in orphanages have different lives than children in general. Living in an orphanage certainly provides challenges for them. Despite the limitations of living in an orphanage, they are also required to continue to have dreams and aspirations for their future. This study examines the association between self-acceptance and self-esteem and their impact on optimism among orphanage children. The hypothesis posits a positive correlation between self-esteem, self-acceptance, and optimism in this particular context. The study employs three validated scales: the optimism scale developed by Scheier et al., the self-acceptance scale proposed by Berger, and the self-esteem scale devised by Rosenberg. Based on purposive sampling, the research participants were 254 children aged 12-18 living in orphanages located in Central Java. The findings reveal a significant positive correlation between self-acceptance, self-esteem, and optimism among the children in the orphanage setting, underscoring that elevated levels of self-esteem and self-acceptance among orphaned children correspond to heightened levels of optimism they possess.